2021
DOI: 10.1016/j.jmh.2021.100060
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health among Venezuelan migrant women at the north western border of Brazil: A qualitative study

Abstract: Background Venezuela has been immersed in an economic and social crisis with a high number of migrant people. An important proportion of Venezuelan migrants have crossed the north western border Brazil-Venezuela were the United Nations High Commissioner for Refugees (UNHCR) has established 13 shelters. Our objectives were to know perspectives and views of Venezuelan migrant women hosted at UNHCR shelters on some SRH issues. Methods We conducted a qualitative study betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 28 publications
1
36
0
6
Order By: Relevance
“…The situation of the migrant women in the Brazilian Amazon region regarding access to SRH care is not different from that previously described by our group which was aggravated by the COVID-19 pandemic ( Bahamondes et al ., 2020 ; Makuch et al., 2021a , Makuch et al., 2021b ; Soeiro et al., 2021a , Soeiro et al., 2021b ). In addition to migration problems, migrant women of reproductive age are vulnerable due to gender inequalities, including unplanned pregnancy due to lack of access to or availability of contraceptive methods ( Olsen et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation of the migrant women in the Brazilian Amazon region regarding access to SRH care is not different from that previously described by our group which was aggravated by the COVID-19 pandemic ( Bahamondes et al ., 2020 ; Makuch et al., 2021a , Makuch et al., 2021b ; Soeiro et al., 2021a , Soeiro et al., 2021b ). In addition to migration problems, migrant women of reproductive age are vulnerable due to gender inequalities, including unplanned pregnancy due to lack of access to or availability of contraceptive methods ( Olsen et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ministério da Saúde 2020 ). Our group conducted three rounds of visits to the Roraima state to interviewed women at reproductive health and adolescents to assess access to SRH care, violence against women, and menstrual poverty ( Bahamondes et al ., 2020 ; Makuch et al., 2021a , Makuch et al., 2021b ; Soeiro et al., 2021a , Soeiro et al., 2021b ). We found difficulties for Venezuelan migrants to access to SRH, among those who requested contraceptives, 63.3% reported that they were unable to obtain the contraceptive that they wished, and 50.6% reported that they were unable to obtain any contraceptives due to lack of availability ( Bahamondes et al ., 2020 ), and according to the perspective of these migrant women violence was part of everyday life ( Makuch et al., 2021a , Makuch et al., 2021b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actions taken to deal with the emergency created by the COVID-19 has created imbalances in healthcare services. The needs for SRH care, the constraints of access to services and the culture barriers, from the perspective of Venezuelan migrant women in the region had been a source of concern ( Albaladejo, 2018 ; UNHCR, 2019; Page et al, 2019 ; Doocy et al, 2019 ; Bahamondes et al, 2020 ; Asociación Profamilia and USAID, 2020; Makuch et al, 2021a ; b ; Soeiro et al, 2021a ; b, Rivillas-García et al, 2021 ). These reports indicated that in Brazil when migrant women had access to services they reported to be satisfied with the attention care mainly obstetric care ( Bahamondes et al, 2020 ; Makuch et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…The needs for SRH care, the constraints of access to services and the culture barriers, from the perspective of Venezuelan migrant women in the region had been a source of concern ( Albaladejo, 2018 ; UNHCR, 2019; Page et al, 2019 ; Doocy et al, 2019 ; Bahamondes et al, 2020 ; Asociación Profamilia and USAID, 2020; Makuch et al, 2021a ; b ; Soeiro et al, 2021a ; b, Rivillas-García et al, 2021 ). These reports indicated that in Brazil when migrant women had access to services they reported to be satisfied with the attention care mainly obstetric care ( Bahamondes et al, 2020 ; Makuch et al, 2021a ). However, data from Colombia indicated that Venezuelan migrant women encounter barriers to access to SRH services (Asociación Profamilia and USAID, 2020; Rivillas-García et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%